Surgical Management of Spinal Osteoblastomas. Issue 1 (April 2016) - Versteeg, Anne; Boriani, Stefano; Varga, Péter Pál; Luzzatti, Alessandro; Fehlings, Michael; Bilsky, Mark; Rhines, Laurence; Reynolds, Jeremy; Dekutoski, Mark; Gokaslan, Ziya; Germscheid, Niccole; Dea, Nicolas; et al.
Introduction: Primary spinal osteoblastomas are rare benign neoplasms which often behave more aggressively than other benign tumors and can present as malignant transformations. Optimal surgical treatment strategies and risk factors for local recurrence and mortality of spinal osteoblastomas remain unclear. The aim of this multicenter cohort study was to assess rates of local recurrence and mortality following surgical intervention for spinal osteoblastomas and to evaluate whether the application of the Enneking classification in the management of these tumors influences local recurrence and mortality. Methods: The AOSpine Knowledge Forum Tumor developed a multicenter ambispective database of patients who underwent surgical intervention for spinal osteoblastoma. Patient demographic, diagnosis, treatment, cross-sectional survival, and local recurrence data were collected. Patients were analyzed in two cohorts based on the Enneking classification of the tumor: Enneking appropriate (EA) and Enneking inappropriate (EI). EA was defined by the final pathology margin matching the Enneking recommended surgical margin, if otherwise, it was defined as EI. Results: Between November 1991 and June 2012, a total of 102 patients diagnosed with a spinal osteoblastoma were identified. Twenty-eight patients were omitted from the analysis due to insufficient follow-up (<12 months) or incomplete survival data, leaving 74 patients for final analysis. The mean follow-up was 4.3 ± 2.8 years in the EI and 4.5 ± 3.3 years in the EA group. Thirteen (18%) patients suffered a local recurrence and six (8%) patients died during the study period. Local recurrence was strongly associated with mortality with a relative risk of 9.4 ( p = 0.007). When adjusting for Enneking appropriateness, the result was not significantly altered. Significant differences were not found between the EA and EI groups for local recurrence and mortality. Conclusion: Upon evaluating the largest multicenter cohort of spinal osteoblastomas to date, the application of the Enneking classification as treatment guide for spinal osteoblastomas could not be confirmed. Considering the consequences of a local recurrence and the strong association of local recurrence with mortality even after adjusting for Enneking appropriateness, en bloc or marginal resection is nevertheless the recommended surgical treatment strategy for spinal osteoblastoma.